LAG-3 expression on peripheral blood cells identifies patients with poorer outcomes after immune checkpoint blockade - Shen, Ronglai; Postow, Michael A; Adamow, Matthew; Arora, Arshi; Hannum, Margaret; Maher, Colleen; Wong, Phillip; Curran, Michael A; Hollmann, Travis J; Jia, Liwei; Al-Ahmadie, Hikmat; Keegan, Niamh; et al. (Science translational medicine, 2021)
Immune checkpoint blocking antibodies are a cornerstone in cancer treatment; however, they benefit only a subset of patients and biomarkers to guide immune checkpoint blockade (ICB) treatment choices are lacking. We designed this study to identify blood-based correlates of clinical outcome in ICB-treated patients. We performed immune profiling of 188 ICB-treated patients with melanoma using multiparametric flow cytometry to characterize immune cells in pretreatment peripheral blood. A supervised statistical learning approach was applied to a discovery cohort to classify phenotypes and determine their association with survival and treatment response. We identified three distinct immune phenotypes (immunotypes), defined in part by the presence of a LAG-3 CD8 T cell population. Patients with melanoma with a LAG immunotype had poorer outcomes after ICB with a median survival of 22.2 months compared to 75.8 months for those with the LAG immunotype ( = 0.031). An independent cohort of 94 ICB-treated patients with urothelial carcinoma was used for validation where LAG immunotype was significantly associated with response ( = 0.007), survival ( < 0.001), and progression-free survival ( = 0.004). Multivariate Cox regression and stratified analyses further showed that the LAG immunotype was an independent marker of outcome when compared to known clinical prognostic markers and previously described markers for the clinical activity of ICB, PD-L1, and tumor mutation burden. The pretreatment peripheral blood LAG immunotype detects patients who are less likely to benefit from ICB and suggests a strategy for identifying actionable immune targets for further investigation.